TAK1 inhibition increases proliferation and differentiation of chick retinal cells - Carrillo, Casandra; Ravi, Vagisha; Tiwari, Sarika; Chernoff, Ellen A.; Belecky-Adams, Teri L. (Frontiers in Cell and Developmental Biology, 2022)
The factors necessary for the differentiation of cell types within the retina are incompletely understood. The transforming growth factor beta (TGF-β) superfamily, including TGF-β1 and 2, the bone morphogenetic proteins, and the activins have all been implicated in differentiation; however, the mechanisms by which these factors affect differentiation are only partially understood. The studies herein focus on a potential role for transforming growth factor β-activated kinase 1 (TAK1), a hub kinase that lies at the intersection of multiple signaling pathways, in the differentiation of cell types within the chick retina. Previous studies have focused predominantly on the role this kinase plays in the inflammation process and axonal growth. TAK1 is downstream of multiple signaling pathways that are critical to development of the central nervous system, including transforming growth factor β (TGFβ), bone morphogenetic proteins (BMPs), and activins. The present study indicates that activated TAK1 is found throughout the developing retina; however, it is localized at higher levels in dividing and differentiating cells. Further, ex ovo retinal studies using TAK1 inhibitor 5Z-7-oxozeaenol increased both progenitor and differentiating cell populations, accompanied by a substantial increase in proliferation and a smaller increase in cell death. These results indicate a unique role for TAK1 in differentiating and proliferating retinal cells.